A Study On Students’ Strategies To Reduce Speaking Anxiety - Juli Astria Mariani; Hamzani Wathoni; Ushuluddin Ushuluddin; Selamet Riyadi Jaelani; Muhammad Husnu (Universitas Palangka Raya, 2023)
The purpose of this study is to know the factors causing students’ speaking anxiety and to know the students’ strategies to reduce their speaking anxiety. This study is focus on factor that caused students’ strategies to reduce their speaking anxiety. This study is qualitative descriptive. The participants of this study were fourth semester of Hamzanwadi University. The researcher took 16 participants. The were gathered through conducting observation, deep interview, and field notes. The results showed that the factors caused students’ speaking anxiety were fear of making mistake, limited exposure to English, and gap of competence. Because of those reasons, the students finally found their strategies to reduce their speaking anxiety such as preparation, relaxation, positive thinking, and peer seeking.